Japan’s Decade Long Tryst with Deflation : What Led a Prospering Economy into a Deflationary Spiral? - Sharma, Sasha (Arthshastra Indian Journal of Economics & Research, 2021)
Japan suffered a deflationary hangover from the great episodic Yen appreciations during the late 1980s into the mid-1990s. The country’s GDP stagnated at low levels during the lost decade, and inflation was persistently low. The period beginning early 1991 and extending to 2001 is popularly referred to as Japan’s lost decade, characterized by deflation. The government’s remedial measure – an expansionary fiscal policy failed to boost the economy. Using the macroeconomic concepts of fiscal policy, monetary policy, and IS-LM model, this note elucidated why an expansionary fiscal policy failed in Japan, despite having the potential to succeed. The analysis also highlighted the impertinence of a credit crunch in the monetary sector on the economic crisis.